Vascular Calcification in an Adolescent Treated with Long-Term Peritoneal Dialysis. (22nd May 2011) - Ekim, Mesiha; Fitoz, Suat; Ozcakar, Z. Birsin; Yalcinkaya, Fatos
Abstract : The reason of high mortality in patients with chronic kidney disease (CKD) is cardiovascular disease and arterial calcification has been accepted as an additive factor on this status. In this report we described vascular and cardiac valvular calcifications in an adolescent on CAPD.